ANALISIS KESANTUNAN BERBAHASA PADA SEGMEN TALK SHOW DALAM ACARA INDONESIA MORNING SHOW NET TV DAN RELEVANSINYA DENGAN PEMBELAJARAN BAHASA INDONESIA DI KELAS X SMA - Amelia Sara Falanta; Moh. Fakhrudin; Joko Purwanto (Jurnal Genre (Bahasa, Sastra, dan Pembelajarannya), 2019)
This study aims to describe (1) compliance with the language politeness principle, (2) violation of the language politeness principle in the talk show segment in the NET Morning TV Show Indonesia and (3) its relevance to learning Indonesian in class X SMA. In this research, the data collection uses competent and free listening techniques and note taking techniques and the data presentation techniques use informal techniques. Based on the results of data analysis, the 76 principles of politeness maxim that were found in this study consisted of 14 maxims of wisdom maxims, 14 maxims of generosity, 19 maxims of praise, 6 of maxims of humility, 19 of maxims of agreement, and 4 of maxims of sympathy . The violations of the language politeness principle found in this study amounted to 25 consisting of 2 violations of wisdom maxim, 3 violations of generosity maxim, 2 violations of praise maxim, 5 violations of humility maxim, 11 violations of agreement maxims, and 2 violations of sympathy maxim. The results of the analysis in the study are relevant to Indonesian language learning in class X SMA, as stated in the basic competency syllabus (KD) 4.3, which is developing the contents of the exposition text (problems, arguments, knowledge, and recommendations) verbally and on basic competencies (KD) 4.10 namely submitting submission, offer, approval and concluding in the negotiating text verbally.